2011
DOI: 10.1523/jneurosci.0873-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Neural Activity across Face-Selective Cortical Regions Is Behaviorally Relevant

Abstract: Interest has increased recently in correlations across brain regions in the resting-state fMRI blood oxygen level-dependent (BOLD) response, but little is known about the functional significance of these correlations. Here we directly test the behavioral relevance of the resting-state correlation between two face-selective regions in human brain, the occipital face area (OFA) and the fusiform face area (FFA). We found that the magnitude of the resting-state correlation, henceforth called functional connectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
119
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 50 publications
18
119
0
Order By: Relevance
“…Several previous studies have reported correlations between performance measures and fMRI FC (22)(23)(24)(25)(26). However, this study, as far as we are aware, is the first to demonstrate that FC, before any exposure, is predictive of performance and acquisition on a novel task.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Several previous studies have reported correlations between performance measures and fMRI FC (22)(23)(24)(25)(26). However, this study, as far as we are aware, is the first to demonstrate that FC, before any exposure, is predictive of performance and acquisition on a novel task.…”
Section: Discussionmentioning
confidence: 43%
“…Hence, resting-state functional connectivity offers a plausible neural correlate of behavioral predisposition to perform a novel task. Moreover, resting-state measures have been correlated with individual performance variability in several cognitive domains (22)(23)(24)(25)(26). However, to our knowledge, no study to date has shown that functional connectivity, measured before training, within cortical circuits later recruited by a novel task, is predictive of future performance.…”
mentioning
confidence: 99%
“…Participants completed two computer-based tasks: the old/new recognition task (Zhu et al, 2011; and the face-inversion task (Zhu et al, 2011), and one paper-based test, the Raven's Advanced Progressive Matrices (RAPM) (Raven et al, 1998). The RAPM test was conducted on a separate day from the computer-based tasks.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…Neuroimaging studies have revealed a well-described face network (FN) comprising brain regions that are coactivated in a variety of face processing tasks (for reviews, see Haxby et al, 2000;Gobbini and Haxby, 2007;Ishai, 2008;Pitcher et al, 2011a), including the fusiform face area (FFA), occipital face area (OFA), superior temporal sulcus (STS), amygdala (AMG), inferior frontal gyrus (IFG), anterior temporal cortex (ATC), and visual cortex (VC) (Calder and Young, 2005;Kanwisher and Yovel, 2006;Gobbini and Haxby, 2007;Liu et al, 2010;Zhang et al, 2012;Zhen et al, 2013). Recent FC studies have shown that some face-selective regions are strongly connected (e.g., the FFA-OFA, FFA-STS, FFA-VC, and STS-AMG) under both task-state and resting-state in the adult brain (Zhang et al, 2009;Turk-Browne et al, 2010;Zhu et al, 2011;DaviesThompson and Andrews, 2012;O'Neil et al, 2014), and effective connectivity of the FFA-OFA and the OFA-STS increases from childhood to adulthood (Cohen Kadosh et al, 2011). Therefore, the coactivated face-selective regions are likely integrated through strengthened FC to form the FN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation